Techniques and Upbringing Parenting Perceived and their Relationship: The concept of Self-Identity and Social Competence among Adolescent Students - Razan Jalal Khalaf Alabaddi (Universitas Negeri Makassar, 2023)
This study aimed to study the perceived techniques of upbringing and parenting , and their relationship to the concept of self-identity and social competence among adolescent students in Jordan. To achieve these goals, the study followed the descriptive method, with a questionnaire as a study tool. This was applied to a sample made up of (500) Public school students in Jordan for the age group between (14-15) years. The study found that the most prominent Techniques for parenting included: dialogue, acceptance, bear the responsibility, and cooperation, for both parents; the degree of the concept of self-identity and social competence was Medium, and the results showed the existence of a positive relationship between parenting and upbringing techniques and the concept of self-identity and Social efficiency.